2010
DOI: 10.1080/17290376.2010.9724958
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stigma among patients receiving antiretroviral treatment: A prospective randomised trial comparing an m-DOT strategy with standard-of- care in Kenya

Abstract: HIV and AIDS remain highly stigmatised. Modified directly observed therapy (m-DOT) supports antiretroviral treatment (ART) adherence but little is known about its association with perceived stigma in resource-constrained settings. In 2003, 234 HIV-infected adults enrolled in a two-arm randomised trial comparing a health centre-based m-DOT strategy with standard self-administration of ART. Data on perceived stigma were collected using Berger's HIV stigma scale prior to starting ART and after 12 months. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 61 publications
2
16
1
3
Order By: Relevance
“…Our primary finding, that there was a trend towards decreasing internalized stigma scores over time on ART, is consistent with both qualitative [2023] and large-sample [24, 25] studies. The effect on stigma was substantive in magnitude and sustained over at least two years of treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our primary finding, that there was a trend towards decreasing internalized stigma scores over time on ART, is consistent with both qualitative [2023] and large-sample [24, 25] studies. The effect on stigma was substantive in magnitude and sustained over at least two years of treatment.…”
Section: Discussionsupporting
confidence: 88%
“…These observations have also been borne out in qualitative studies showing that treatment was associated with improved self-image among HIV-infected persons in South Africa and Zimbabwe [2023]. Large sample studies have yielded conflicting findings about the extent to which treatment reduces the stigma of HIV [2427]. These studies were restricted to relatively brief periods of data collection, however, and were unable to ascertain the robustness of any observed trends.…”
Section: Introductionmentioning
confidence: 99%
“…In Mombasa, the network of positive people is small and poorly organized and, our previous study showed that PLHIV were reluctant to reveal their status and were poorly networked, with high levels of internalized stigma. This has also been reported by other African studies [11,12,28]. Our study sample consisted of 76% female participants.…”
Section: Discussionsupporting
confidence: 74%
“…Health workers identified PLHIV in their community and asked these PLHIV to bring in others they knew. As our previous study showed us that PLHIV in Mombasa are relatively isolated due to stigma and disclosure concerns [28], health workers were permitted to add new 'seeds' if PLHIV were unable to bring in peers.…”
Section: Methodsmentioning
confidence: 99%
“…PLHIV in Mombasa are poorly networked and reluctant to reveal their status 17 . As there is no listing of PLHIV in the community, each CHW first identified 2 to 3 unrelated index PLHIV and then asked the index PLHIVs to connect the CHW to other PLHIV they knew.…”
Section: Methodsmentioning
confidence: 99%